The Life Cycle of the Acropora Coral-Eating Flatworm (AEFW), Prosthiostomum acroporae; The Influence of Temperature and Management Guidelines - Barton, Jonathan A.; Hutson, Kate S.; Bourne, David G.; Humphrey, Craig; Dybala, Cat; Rawlinson, Kate A. (Frontiers in Marine Science, 2019)
As coral aquaculture is increasing around the world for reef restoration and trade, mitigating the impact of coral predators, pathogens and parasites is necessary for optimal growth. The Acropora coral-eating flatworm (AEFW), Prosthiostomum acroporae (Platyhelminthes: Polycladida: Prosthiostomidae) feeds on wild and cultivated Acropora species and its inadvertent introduction into reef tanks can lead to the rapid death of coral colonies. To guide the treatment of infested corals we investigated the flatworm’s life cycle parameters at a range of temperatures that represent those found in reef tanks, coral aquaculture facilities and seasonal fluctuations in the wild. We utilized P. acroporae from a long-term in vivo culture on Acropora species to examine the effects of temperature (3°C increments from 21-30°C) on flatworm embryonation period, hatching success, hatchling longevity, and time to sexual maturity. Our findings show that warmer seawater shortened generation times; at 27°C it took, on average, 11 days for eggs to hatch, and 35 days for flatworms to reach sexual maturity, giving a minimum generation time of 38 days, whereas at 24°C the generation time was 64 days. Warmer seawater (24–30°C) also increased egg hatching success compared to cooler conditions (21°C). Taken together these results indicate that warmer temperatures lead to higher population densities of P. acroporae. Temperature significantly increased the growth rate of P. acroporae, with individuals reaching a larger size at sexual maturity in warmer temperatures, but it did not influence hatchling longevity. Hatchlings, which can swim as well as crawl, can survive between 0.25 to 9 days in the absence of Acropora, and could therefore disperse between coral colonies and inter-connected aquaria. We used our data to predict embryonation duration and time to sexual maturity at 21°C-30°C, and discuss how to optimise current treatments to disrupt the flatworm’s life cycle in captivity.